Optimal Control of Switching Topology Networks. (7th July 2014) - Mojica-Nava, Eduardo; Salgado, Jimmy; Tellez, Duvan; Lopez, Alvaro
Abstract : We present an extension of a previously proposed approach based on the method of moments for solving the optimal control problem for a switching system considering now a continuous external input. This method is based on the transformation of a nonlinear, nonconvex optimal control problem, into an equivalent optimal control problem with linear and convex structure, which allows us to obtain an equivalent convex formulation more appropriate to be solved by high-performance numerical computing. Finally, the design of optimal logic-based controllers for networked systems with a dynamic topology is presented as an application of this work.